Twitter Data Analysis on Halal Labeling: Insights for the Food Industry in Indonesia - Izza, Nadia Nurul; Fitria, Lia; Arsyi, Muhammad; Nugraha, Fajar (SMART Insight, 2023)
This research uses text data mining techniques and the Drone Emprit Academic (DEA) system to identify and collect current problems related to the Halal label. The data analyzed includes 2,665 conversations from August 19, 2022 to March 15, 2023. The results show that conversations around the Halal label are closely related to the popular food franchise industry, with words such as